Viewing sports online together? Psychological consequences on social live streaming service usage. Issue 5 (November 2020) - Kim, Han Soo; Kim, Minjung
Highlights: We provided a comprehensive understanding of social live streaming services (SLSSs) in sport contexts. We explored the expected gratifications of sport fans who use SLSSs for watching sport events. Four expected gratifications enhanced flow and satisfaction, which increased social well-being and decreased loneliness. We examined the moderating role of team identification on the relationship between affective gratification and flow in using SLSSs. Abstract: Social live streaming services (SLSSs) have recently been introduced as a new type of synchronous social networking services for sport fans. Given the popularity of these innovations, the authors examined how the use of SLSSs can augment users' social well-being and mitigate loneliness through the mechanisms of team identification, flow experiences, and satisfaction with SLSSs. To this end, the researchers collected data from 231 SLSS users who watched sport events over the SLSS platforms during the past 12 months. Results indicated that four types of gratification expectations positively influenced the users' flow states. Among highly identified users with their preferred teams, affective gratification exerted the greater impact on the flow, predicting satisfaction with SLSSs. Such satisfaction enabled the users to enhance their social well-being and ease their feelings of loneliness. This study provides empirical evidence and new insights that elevate our understanding of SLSSs for sports content.